Continuum mechanical modeling of laser‐pulsed heating in polycrystals: A multi‐physics problem of coupling diffusion, mechanics, and thermal waves. Issue 6 (20th January 2014) - Bargmann, S.; Favata, A.
Abstract This contribution introduces a geometrically nonlinear, continuum thermomechanical framework for pulsed laser heating in crystalline matter: a physical process which is characterized by a non‐Fourier like heat propagation and defect diffusion. The key objective of this work is to derive the highly nonlinear and strongly coupled system of governing equations describing the multi‐physical behavior from fundamental balance principles. A general form for the Helmholtz energy is proposed and the resulting constitutive laws are derived from logical, thermodynamically consistent argumentation. The approach adopted to derive the governing equations is not entirely specific to laser induced heating, rather it encompasses a wide range of applications wherein heat conduction, species diffusion, and finite elastic effects are coupled. The present theory is thus applicable to the generality of models for thermal and mechanical waves: an area of increasing research interest. A numerical example is presented for the fully coupled, nonlinear and transient theory.